Just South of Zion : The Mormons in Mexico and Its Borderlands - Tamez, Jared M., 1981-; Dormady, Jason, 1975- (Book collections on Project MUSE., 2015)
Just South of Zion assembles new scholarship on the first century of Mormon history in Mexico, from 1847 to 1947.